Analysis of the Role of TpUB05 Antigen from Theileria parva in Immune Responses to Malaria in Humans Compared to Its Homologue in Plasmodium falciparum the UB05 Antigen - Dinga, J.N.; Perimbie, S.N.; Gamua, S.D.; Chuma, F.N.G.; Njimoh, D.L.; Djikeng, Appolinaire; Pelle, Roger; Titanji, V.P.K. (MDPI, 2020)
Despite the amount of resources deployed and the technological advancements in molecular biology, vaccinology, immunology, genetics, and biotechnology, there are still no effective vaccines against malaria. Immunity to malaria is usually seen to be species- and/or strain-specific. However, there is a growing body of evidence suggesting the possibility of the existence of cross-strain, cross-species, and cross-genus immune responses in apicomplexans. The principle of gene conservation indicates that homologues play a similar role in closely related organisms. The homologue of UB05 in Theileria parva is TpUB05 (XP_763711.1), which has been tested and shown to be associated with protective immunity in East Coast fever. In a bid to identify potent markers of protective immunity to aid malaria vaccine development, TpUB05 was tested in malaria caused by Plasmodium falciparum. It was observed that TpUB05 was better at detecting antigen-specific antibodies in plasma compared to UB05 when tested by ELISA. The total IgG raised against TpUB05 was able to block parasitic growth in vitro more effectively than that raised against UB05. However, there was no significant difference between the two study antigens in recalling peripheral blood mononuclear cell (PBMC) memory through IFN-γ production. This study suggests, for the first time, that TpUB05 from T. parva cross-reacts with UB05 from P. falciparum and is a marker of protective immunity in malaria. Hence, TpUB05 should be considered for possible development as a potential subunit vaccine candidate against malaria.